Determination of Suitable KCl Polymer Mud Properties for POK Field - Puri Wijayanti; Bayu Satiyawira; Andry Prima; Arinda Ristawati; Foggie Sciorra (Penerbitan Universitas Trisakti, 2021)
Most oil and gas wellbores are drilled using water based mud (WBM), but this is the case when drilling through non-reactive formations that does not contain swelling shale. In reactive shale formation, KCl Polymer additive should be added to the mud. It will provide a source of potassium ions which will help stabilizing the reactive shale. So that the swelling process is minimized. The basis of the KCL polymer mud system is the polymer used as a wrapper for rock pieces during borehole cleaning process. In the wells in the POK Field, the use of polymer KCL mud is evaluated on trajectories of 17½